Analysis of local invasion and regional spread in malignant sublingual gland tumour: Implications for surgical planning. Issue 10 (October 2021) - Park, W.; Park, M.; Choi, K.; Heo, Y.; Choi, S.Y.; Cho, J.; Ko, Y.-H.; Jeong, H.-S.
Abstract: Malignant tumours arising from the sublingual glands are very rare, and the extent and frequency of local invasion or regional spread in malignant sublingual gland tumour (MSLT) has not been fully studied due to the disease rarity. To provide comprehensive features of local and regional spread of MSLT, we reviewed 20 surgical cases for detailed pathological analyses among 26 cases diagnosed as having primary MSLT. Adenoid cystic carcinoma (ACC) was the most common pathological subtype, followed by mucoepidermoid carcinoma. Disease-free and overall survivals at 5 years were 76.1 % and 77.7 %, respectively. High-grade malignant tumours and grade 2–3 ACC accounted for 41.7 % and 85.7 %. Clinical and pathological extraparenchymal extensions were found in 34.6 % and 80.0 %, respectively. Tumour invasion to the lingual nerve and submandibular gland/ductal system were also detected in 40.0 % and 28.6 %. The incidences of lingual nerve invasion in ACC and ACC ≥4 cm were 30.8 % and 42.9 %. Regional nodal involvement occurred in seven of 26 cases, and all metastatic lymph nodes were found in neck levels Ib and IIa. In summary, a significant portion of MSLT cases consisted of high-grade tumours and grade 2–3 ACC; therefore local invasion into adjacent structures should be cautiously evaluated in cases of MSLT.